Ecology of bat flies in Singapore: A study on the diversity, infestation bias and host specificity (Diptera: Nycteribiidae) - Zong Xian Lim; Alan T. Hitch; Benjamin P. Y.-H. Lee; Dolyce H.W. Low; Erica Sena Neves; Sophie A. Borthwick; Gavin J.D. Smith; Ian H. Mendenhall (International Journal for Parasitology: Parasites and Wildlife, 2020)
Bat flies are highly-specialized, hematophagous arthropods that are globally ubiquitous. There is little published research on bat flies (Diptera: Nycteribiidae) in Singapore and understanding the diversity of nycteribiids, host association and infestation rates can provide insight into this host-ectoparasite relationship. Nycteribiids were collected from bats trapped in Singapore (2011–2016) and identified using morphological keys. Host-ectoparasite relationships were investigated with logistic regression and Bayesian poisson regression. Nycteribiids were found to be monoxenously associated with their host bat species and host age, sex, species, and BBCI appear to contribute to differences in prevalence and intensity. Differences in host specificity between bat fly species in Singapore and their conspecifics in less disturbed habitats with higher bat biodiversity, such as Malaysia, Philippines and Thailand, suggest that the high host specificity in Singapore derives from the paucity of suitable hosts and abundance of single species roosts and not from their coevolved restrictions to them.